RESISTENSI OBAT MALARIA: MEKANISME DAN PERAN OBAT KOMBINASI OBAT ANTIMALARIA UNTUK MENCEGAH - Simamora, Dorta; Fitri, Loeki Enggar (Fakultas Kedokteran Universitas Brawijaya, 2007)
Multi drug resistance (MDR) of malariae parasite iscaused by decreasing ability of some antimalarial drugs examples chloroquine, mefloquine, antifolate and atovaquone to Plasmodium. Resistance to artemisin has not beenfound yet. Antimalaria drug resistance happened because some factors especially : genetic factor (gene mutation) of the Plasmodium. Mechanism pathway of resistance differsin location, because the different target drug action. Resistance migh be reduce by using combination therapy. Key words: resistance, Plasmodium falciparum, antimalaria combination